2012
DOI: 10.9753/icce.v33.management.40
|View full text |Cite
|
Sign up to set email alerts
|

Moving Gravel Body Method to Control Downcoast Erosion

Abstract: The concept of the moving gravel body (MGB) method, in which topographic changes are controlled by beach nourishment using gravel, was introduced, using the contour-line-change model considering changes in grain size. The model was applied to the Fuji coast, assuming that coarse materials were nourished on a straight coast wherein a predominant longshore sand transport develops. The grain size that is effective for the recovery and maintenance of the shoreline and that does not cause further downcoast erosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In this perspective is very important to better understand how gravel fill material evolves over time when deployed on a native sandy beach surface. Several project have been made choosing gravel as nourishment material to counteract erosion processes on native sandy beaches (Takagi et al, 2001;Cammelli et al, 2004;Kumada et al, 2010;Bertoni and Sarti, 2011;Ishikawa et al, 2012), but no considerations are made on shape nor shape evolution of fill material. The real issue of gravel nourishment is the supply of coarse gravel (pebbles and cobbles), thus many coastal managers chose to replenish using fine gravel or sand-gravel mixes (Williams, 2005;Moses and Williams, 2008).…”
Section: Consideration On Fill Materials For Gravel Nourishmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective is very important to better understand how gravel fill material evolves over time when deployed on a native sandy beach surface. Several project have been made choosing gravel as nourishment material to counteract erosion processes on native sandy beaches (Takagi et al, 2001;Cammelli et al, 2004;Kumada et al, 2010;Bertoni and Sarti, 2011;Ishikawa et al, 2012), but no considerations are made on shape nor shape evolution of fill material. The real issue of gravel nourishment is the supply of coarse gravel (pebbles and cobbles), thus many coastal managers chose to replenish using fine gravel or sand-gravel mixes (Williams, 2005;Moses and Williams, 2008).…”
Section: Consideration On Fill Materials For Gravel Nourishmentsmentioning
confidence: 99%
“…Nourishment projects with coarse material (i.e. gravel or shingle) started in England in small scales and occasionally already in the 1950s and began to proliferate in the 1970s (Hanson et al, 2002;Moses and Williams, 2008); currently they are not only used to contrast erosion on natural coarse-grained beaches but also as an attempt at stabilizing originally sandy beaches (Takagi et al, 2001;Cammelli et al, 2004;Kumada et al, 2010;Bertoni and Sarti, 2011;Ishikawa et al, 2012). However, an issue often present is the availability of coarse material from sea-bed reservoirs, as this type of sediment is only available in continental shelf seas, where large fluvio-glacial deposits are available, like in the North Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Ishikawa et al (2011) investigated beach changes after an extensive nourishment using 3.5×10 5 m 3 of a mixture of sand and gravel at the Hamamatsu-shinohara coast facing the Pacific Ocean, and they showed their effectiveness. Ishikawa et al (2012) further proposed the moving gravel body method using the contour-line change model, in which the change in grain size is evaluated as the change in the equilibrium slope. They showed that when coarse material is nourished on sandy beaches with a predominant longshore sand transport, the downcoast of the nourishment area is eroded, because the movability of gravel is much smaller than that of sand, and gravel is preferentially deposited on the foreshore.…”
Section: Introductionmentioning
confidence: 99%